Phenomenology of shadow teaching in the Philippines - Buenrostro, Janine S.
The Philippine special education sector utilizes various practices to ensure that children with special needs (CSN) are included in the general education classrooms. One of these practices is called Shadow Teaching, an instructional scheme conceptualized to include a shadow teacher inside the general education classroom to assist the CSN. Despite being utilized by inclusive schools, shadow teaching as a practice has yet to be formally adopted. Its identity and characteristics, how it is practiced and implemented, and the challenges of its implementation are yet to be defined. Using phenomenology, this study sought to contextualize the practice of shadow teaching through the lived experiences of six shadow teachers from therapy centers and schools in Metro Manila.